Tetramethylammonium hydrogen terephthalate - Dolatyari, Leila (International Union of Crystallography, 2012)
The asymmetric unit of the title salt, C(4)H(12)N(+)·C(8)H(5)O(4) (−), contains one half of a tetramethylammonium cation and one half of a hydrogen terephthalate monoanion. The N atom of the ammonium cation lies on a twofold rotation axis and the centre of mass of the terephthalate anion is on a centre of inversion. In the crystal, the centrosymmetric terephthalate ions are linked by a very short symmetric O—H⋯O hydrogen bond [O⋯O = 2.4610 (19) Å] into a one-dimensional polymeric chain along [1-12]. The tetramethylammonium cations and terephthalate anions are then connected through a pair of bifurcated acceptor C—H⋯O hydrogen bonds, generating a three-dimensional supramolecular network. The carboxylate groups at both ends of the terephthalate anion are charge-shared with an equal probability of 0.5.